Siderophore-Mediated Iron Dissolution from Nontronites Is Controlled by Mineral Cristallochemistry - Parrello, Damien; Zegeye, Asfaw; Mustin, Christian; Billard, Patrick (Frontiers in Microbiology, 2016)
Bacteria living in oxic environments experience iron deficiency due to limited solubility and slow dissolution kinetics of iron-bearing minerals. To cope with iron deprivation, aerobic bacteria have evolved various strategies, including release of siderophores or other organic acids that scavenge external Fe(III) and deliver it to the cells. This research investigated the role of siderophores produced by Pseudomonas aeruginosa in the acquisition of Fe(III) from two iron-bearing colloidal nontronites (NAu-1 and NAu-2), comparing differences in bioavailability related with site occupancy and distribution of Fe(III) in the two lattices. To avoid both the direct contact of the mineral colloids with the bacterial cells and the uncontrolled particle aggregation, nontronite suspensions were homogenously dispersed in a porous silica gel before the dissolution experiments. A multiparametric approach coupling UV-vis spectroscopy and spectral decomposition algorithm was implemented to monitor simultaneously the solubilisation of Fe and the production of pyoverdine in microplate-based batch experiments. Both nontronites released Fe in a particle concentration-dependent manner when incubated with the wild-type P. aeruginosa strain, however iron released from NAu-2 was substantially greater than from NAu-1. The profile of organic acids produced in both cases was similar and may not account for the difference in the iron dissolution efficiency. In contrast, a pyoverdine-deficient mutant was unable to mobilise Fe(III) from either nontronite, whereas iron dissolution occurred in abiotic experiments conducted with purified pyoverdine. Overall, our data provide evidence that P. aeruginosa indirectly mobilise Fe from nontronites primarily through the production of pyoverdine. The structural Fe present on the edges of Nau-2 rather than Nau-1 particles appears to be more bio-accessible, indicating that the distribution of Fe, in the tetrahedron and/or in the octahedron sites, governs the solubilisation process. Furthermore, we also revealed that P. aeruginosa could acquire iron when in direct contact with mineral particles in a siderophore-independent manner.